It's a wise child who knows his own father: the figure of the American family in The Last Samurai and Extremely Loud and Incredibly Close. Issue 12 (1st December 2020) - Namiki, Yuki
ABSTRACT: The image of a boy growing up and making sense of the world is a quintessential cultural icon. As R. W. B. Lewis argued in his classic discussion of 'the American Adam', children, typically boys entering puberty, discovering the world and defining themselves as new men, exemplify for Americans their growing nation. Parents, especially maternal figures, are seldom included in the American Bildungsroman, other than as obstacles or shadows in the background. However, as Amy Kaplan suggested in A Child of One ' s Own, parenthood has actually been a central topic in modern American literature, and revisiting the concept of parenthood and family has been an important theme in the contemporary American Bildungsroman. This essay will examine two twenty-first-century American Bildungsromane, both featuring prepubescent boys rediscovering their families, and their mothers in particular. One is Helen Dewitt's The Last Samurai (2000), and the other is Jonathan Safran Foer's Extremely Loud and Incredibly Close (2007). Each story features a bright child who is innocent and mature at the same time and is in search of a non-existent father. Examining their similarities and differences will serve as an important starting point in discussing family figures in contemporary culture.